In vivo CD8+ T cell control of immunodeficiency virus infection in humans and macaques. - Asquith, B; Mclean, A (2007)
Forty million people are estimated to be infected with HIV-1, and only a small fraction of those have access to life-prolonging antiretroviral treatment. As the epidemic grows there is an urgent need for effective therapeutic and prophylactic vaccines. Nonhuman primate models of immunodeficiency virus infection are essential for the preclinical evaluation of candidate vaccines. To interpret the results of these trials, comparative studies of the human and macaque immune responses are needed. Despite the widespread use of macaques to evaluate vaccines designed to elicit a CD8(+) cytotoxic T lymphocyte (CTL) response, the efficiency with which CTL control immunodeficiency virus infections has not been compared between humans and macaques, largely because of difficulties in assaying the functional CTL response. We recently developed a method for estimating the rate at which CTLs kill cells productively infected with HIV-1 in humans in vivo. Here, using the same technique, we quantify the rate at which CTLs kill infected cells in macaque models of HIV infection. We show that CTLs kill productively infected cells significantly faster (P = 0.004) and that escape variants have significantly higher fitness costs (P = 0.003) in macaques compared with humans. These results suggest that it may be easier to elicit a protective CTL response in macaques than in humans and that vaccine studies conducted in macaques need to be interpreted accordingly.